Qualitative evaluation of factors influencing adherence to virtual exercise programs for people with physical disabilities - Mintz, Madison; Ferguson, Christine; Dayton, Leigh Anne Bray; Wilroy, Jereme; Rimmer, James H. (Frontiers in Rehabilitation Sciences, 2024)
Virtual community-based programming for people with disabilities has become a popular method for advocating for health promotion, specifically exercise, for people with disabilities (PWD). Using theoretical frameworks to better understand the perspective of PWD who participate in virtual exercise programs allows strategies of implementation following completion of virtual exercise programs. The objective of this study was to examine the effect adherence had on perceptions, experiences, and post-program exercise maintenance in participants with disabilities. Eight qualitative interviews were conducted in highly adherent participants using the Social Cognitive Theory (SCT). Interviews were recorded on Zoom, transcribed using Microsoft 365, and analyzed using NVivo software. Data were analyzed by the primary author and an independent coder to increase rigor and reduce bias. Thirty-five unique codes were generated from transcribed interviews. Member-checking was employed to increase internal validity; 100% of participants agreed with the findings. Results demonstrate an overall positive experience in the virtual exercise program, noting specific facilitators (i.e., knowledgeable instructor, program provided equipment, etc.) and barriers (i.e., limited physical space at home to exercise, other participant's attitudes, etc.) of participating. Impressionably, 100% of participants maintained exercise following their time within the virtual exercise program.